Analisis Penerapan Lean Six Sigma dalam Meningkatkan Efektifitas Laboratorium Rumah Sakit: A Literature Review - Prasetio Hadi Pratama; Nadya Salsabila; Siti Humira Syarif; Acim Heri Iswanto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Hospital quality must be improved for the benefit of patients because the main task of a hospital or health care facility is to provide medical services to patients. The laboratory is part of the medical service that provides services such as making a diagnosis, providing treatment, monitoring the results of treatment, and establishing a patient's diagnosis. This article was prepared using the literature review method by outlining the contents of the research results that already existed and in accordance with the topic of discussion regarding the analysis of the application of lean six sigma in increasing the effectiveness of hospital laboratories with the lean method using Google Scholar, Emerald, and Pubmed with the keywords lean six sigma, laboratory, and hospital or lean six sigma, laboratory, and hospital. Based on the results of the literature review, it was found that the activities carried out in the laboratory still show activities that do not generate added value or waste. This is because the technique for handling examination specimens sent from inpatients and the emergency room has not been effective, and the mechanism for handing over specimens between health workers has not been effective. Research (Ibrahim et al., 2022) shows the implementation of lean six sigma can improve the timeliness of inpatients for routine CBC tests in the laboratory and minimize patient dissatisfaction.